Electroactive, Mediating and Thermosensitive Microgel Useful for Covalent Entrapment of Enzymes and Formation of Sensing Layer in Biosensors. Issue 12 (10th October 2018) - Marcisz, Kamil; Kaniewska, Klaudia; Mackiewicz, Marcin; Nowinska, Anna; Romanski, Jan; Stojek, Zbigniew; Karbarz, Marcin
Abstract: Thermosensitive microgel particles based on the polymeric network synthesized from N ‐isopropylacrylamide, sodium acrylate and N, N′ ‐bisacryloylcystine have been functionalized with aminoferrocene, a mediatior, and a model enzyme‐glucose oxidase (GOx). The product was very stable. A thin coating of that material has been successfully attached to the glassy carbon electrode surface to form a sensing layer. A temperature increase to a value higher than the volume phase transition temperature led to a substantial increase in the amperometric signal. That behavior was well switchable. The amperometric signal was linearly dependent on glucose concentration in the physiological concentration range. It appeared that the synthesized and functionalized microgel was a kind of microreactor and might be very useful for the construction of the platforms that can enhance the activity of enzymes in biosensors. Abstract :